Sustaining Peatlands: Community-driven Fire Reduction and Land Management - Arisanty, Deasy; Hastuti, Karunia Puji; Putro, Herry Porda Nugroho; Aristin, Nevy Farista; Angriani, Parida; Alviawati, Eva; ‎ , Syahril (KnE Social Sciences, 2024)
This study aimed to analyze sustainable peatland management to reduce the risk of peatland fires. Data were collected through observations and interviews with 20 informants, including farmers, civil servants, heads of government offices, and the Masyarakat Peduli Api (MPA) or Fire Care Community. Findings confirmed that knowledge of peatland characteristics, economic morals, local wisdom, and adaptation carried out by the community has an impact on sustainable peatland management. Local knowledge about the peatland, economic morals, and adaptations have been passed on from generation to generation by reducing land preparation by burning and using appropriate agricultural equipment and farming systems. Managing peatlands while maintaining local wisdom through the tapulikampar system is a better option to reduce the risk of land fires. If the community continues to maintain the local values in managing peatlands, the risk of fires on peatlands can be reduced. Keywords: Ce4ommunity, land management, sustainable, fire reduction, peatland